Pengaruh Motivasi Kerja, Gaya Kepemimpinan, dan Lingkungan Kerja Terhadap Kinerja Karyawan di Bale Ayu Resto - Cahyani, Dina Nur; Dina Nur Cahyani (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the influence of work motivation, leadership style, and work environment on employee performance at Bale Ayu Resto. Using a quantitative approach with a survey involving 41 respondents, the results of the analysis show that work motivation and work environment have a significant positive influence on employee performance, with significance values ​​of 0.003 and 0.008, respectively. On the other hand, leadership style does not show a significant influence on employee performance, with a significance value of 0.507. Overall, the three independent variables together affect employee performance, as reflected in the F value of 6.679 and the coefficient of determination (R²) of 0.761. These results indicate that work motivation and work environment are the main factors that affect performance, while leadership style needs further attention to improve employee work results.